Optimization of methodology of education, self- education and level knowledge control of pharmacists-interns for «Krok 3. Pharmacy» - Ya. O. Hrynkiv; I. Yu. Revyatskyy; O. M. Zaliska (The State Expert Center of the Ministry of Health of Ukraine, 2019)
Since 2017 exam «Krok 3. Pharmacy» (pilot in 2017-2018) has been included to the system of licensed integrated exams for pharmacists-interns specialty «General Pharmacy». Which introduced some adjustments to the educational process at the postgraduate stage of education. The task was to review the existing methods of education, self-education and level knowledge control of pharmacists-interns to «Krok 3. Pharmacy» at the Department of organization and economics of pharmacy, drug technology and pharmacoeconomics FPE of Danylo Halytskyy Lviv National Medical University and determined possible directions for their optimization. The objects of the research were the processes of education, self-education and level knowledge control of pharmacists-interns for the exam «Krok 3. Pharmacy»; the results of conducted pre-tests pharmacists-interns for 2017-2019; the results of anonymous survey of students pharmacy faculty and pharmacists-interns on possible areas of optimization of the above processes. It was used methods of statistical processing of the results of an anonymous questionnaire the Google form and the results of pre-tests to «Krok 3. Pharmacy» for pharmacists-interns 2017-2019 learning years. It was found that a significant majority of pharmacists-interns begin preparation for «Krok 3. Pharmacy» 1-3 months before the date of exam. Questions on clinical pharmacy and pharmaceutical technology are easier, pharmaceutical analysis of drugs and special training are the most difficult. It was confirmed that, there is no a direct relationship between the complexity of studying questions and the pre-test results of subjects. 57% of respondents consider that pre-testing should be conducted only online; 25% - only on paper; 18% - by two methods: on paper and online. It was determined promising areas for further optimization preparation of the pharmacists-interns were determined on the basis of the obtained results: education period; formation of blocks of test tasks for the «MISA» system and paper by the quantity of questions and by subjects; use computer information technologies for self-education for «Krok 3. Pharmacy».